Terrain Database Correlation Assessment Using an Open Source Tool - Oyama, Leonardo Seiji; Peres, Sérgio Simas Lopes; Rodrigues, Carlo Kleber da Silva; Goldiez, Brian (My University, 2017)
Configuring networked simulators for training military teams in a distributed environment requires the usage of a set of terrain databases to represent the same training area. The results of simulation exercises can be degraded if the terrain databases are poorly correlated. A number of methodologies for determining the correlation between terrain databases have been developed, by both government and industry, aiming at Verification, Validation & Accreditation of distributed simulations involving different simulators. However, there are few computational tools for this task and most of them were developed to address government needs, have limited availability, and handle specific digital formats. The goal of this paper is thus to present a novel open source tool developed as part of an academic research project. This tool analyzes a pair of terrain databases generating numeric data suitable for statistical analysis, as well as identifies specific areas where correlation may be an issue by using a configurable threshold. The analysis takes into consideration line-of-sight correlation differences between the databases. The sample size and characteristics of the line-of-sight tests, for instance elevation and azimuth, are selectable via a graphical user interface which also provides a 3D visualization of the terrain databases. Being open source, programmers may add more capabilities to the tool, such as including support to more digital formats or implementing new software methods to measure the correlation between terrain databases. Plans for extending the tool’s capabilities and its possible utilizations are also included herein.